A novel toxic alkaloid from poison hemlock (Conium maculatum L., Apiaceae): identification, synthesis and antinociceptive activity - DE SOUSA MENEZES, FABIO (My University, 2012)
2-Pentylpiperidine, named conmaculatin, a novel volatile alkaloid related to coniine was identified from the renowned toxic weed Conium maculatum L. (Apiaceae). The structure of conmaculatin was corroborated by synthesis (8 steps starting from cyclohexanol, overall yield 12%). Conmaculatin?s strong peripheral and central antinociceptive activity in mice was observed in a narrow dose range (10-20 mg/kg). It was found to be lethal in doses higher than 20 mg/kg.
PUBLISHED
Keywords: Pharmacology; Conium maculatum L; 2-pentylpiperidine; Volatile alkaloid; Immunology, Inflammation & Infection; International Development